BIOSTRATIGRAPHIC AND PALEOECOLOGICAL CHARACTERISTICS OF ALB FACIAL FORMATIONS OF NEAR-DNISTER AREA - KYSELEVYCH, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The paper deal with facial fetures of sea sediments of middle and upper substages of Albian stage of Cretaceous system in Middle Dnister area. There are listed biostratigraphycal affinities of that rocks and paleoinvirontmental affinities development of sea basins.